Relationship of executive functions and physical abilities in elite soccer players - Scharfen, H.-E.; Memmert, D. (German Journal of Exercise and Sport Research, 2022)
Objectives: This study investigated the relationship of executive functions and physical abilities in youth and adult elite soccer players. Design and methods: In all, 172 elite soccer players (12-34 years of age) performed a computer-based test battery assessing multiple-object tracking, working memory capacity, cognitive flexibility, and inhibition. Another series of tests measured endurance-performance at the individual anaerobic threshold (IAT), ability to repeatedly perform intense exercises (RIEA), and maximal anaerobic performance parameters (squat jump, counter movement jump, drop jump quotient, sprint time). Results: Executive functions and maximal anaerobic parameters showed small to moderate correlations for example, working memory capacity and cognitive flexibility with sprint, countermovement- and drop jump along with a correlation of inhibition and RIEA. Conclusion: These findings favor specific motor-cognition associations rather than a one-fits-all association. Specifically, sprint and jump seem to be more closely linked to cognitive skills than endurance parameters and represent fundamental associations across several age groups